Analysis of surfaces for characterization of fungal burden - Does it matter? - Viegas, Carla (2017)
Mycological contamination of occupational environments can be a result of fungal spores' dispersion in the air and on surfaces. Therefore, it is very important to assess it in both types of the samples. In the present study we assessed fungal contamination in the air and in the surface samples to show relevance of surfaces sampling in complementing the results obtained in the air samples.